Bratislavia dadayi (Michaelsen 1905) (Annelida, Clitellata, Naididae): discovery of an alien oligochaete in a technogenic fresh water body in Ukraine - Gusakov, Vladimir A.; Sylaieva, Anzhelika A. (Zootaxa, 2019)
A non-native oligochaete, Bratislavia dadayi (Michaelsen 1905), is recorded from a water body of the cooling system of the Khmelnitsky Nuclear Power Plant (Ukraine). This is the first registration of this species in the central part of the European continent, far from sea and river navigable waterways. The only previous record of B. dadayi in Europe had been from a Belgian estuary. The occurrence in samples taken over several years, and the presence of sexually mature individuals in the Ukrainian population indicate the worm’s successful naturalization in the new habitat. In this paper, we analyze the species’ morphology and abundance in the Ukrainian population and discuss its ecology, current and potential distribution.